A Comparative Study of the Impact of Himalayan Singing Bowls and Supine Silence on Stress Index and Heart Rate Variability - Gunjan, Y Trivedi; Banshi, Saboo (Journal of Behavior Therapy And Mental Health, 2019)
Introduction Sound vibrations have a profound impact on the body and the mind with evidence confirming reduced anxiety and increased wellbeing. The likely reason for driving the benefit is relaxation. The Himalayan Singing Bowls, used for therapeutic intervention to enhance the individual’s emotional & physical wellbeing, may facilitate faster and deeper relaxation as compared to simple, supine relaxation. Aim of the Study The study aimed to validate the hypothesis that short 20 minutes sessions to relax with the help of the Himalayan Singing Bowl (HSB) could provide better depth of relaxation as compared to Supine Silence (SS) based on the objective assessment of physiology parameters i.e. Stress Index & Heart Rate Variability (HRV).  Methods Seven metal Himalayan singing bowls were used in a particular sequence learned from an expert teacher for 16 subjects. The SS group consisted of 17 subjects. The HRV data was measured by the Emwave Pro device and analyzed using Kubios HRV Premium software. The analysis compared key HRV parameters within and between the groups. Result Overall, as expected, both groups achieved relaxation as measured by changes in HRV parameters. However, further analysis confirmed a more consistent relaxation, as measured by a statistically significant reduction in stress index and an increase in HRV, for HSB group. The HSB group achieved more consistent depth of relaxation during each subsequent 5 minutes interval throughout the session as compared to SS group.  Conclusion The study confirms that singing bowls sessions can be leveraged as a tool for inducing good quality relaxation response (increased parasympathetic tone, reduced stress) to facilitate healing and energy recovery in just 20 minutes and achieve significant health benefits. More comprehensive studies must be conducted to further evaluate the findings with more sample size, different methods of relaxation and varied demographics.
Keywords: Stress Index (SI); Heart Rate Variability (HRV); Himalayan Singing Bowls (HSB); Relaxation Response; Silence; Sound Healing